2017
DOI: 10.1021/acs.jpcc.7b07541
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Capture Partner Molecules in Highly Loaded PEI Sorbents

Abstract: Decoupling amine loading from diffusion resistance is one of the main challenges in the development of immobilized amine CO 2 sorbents. Water has been reported to serve this goal, alleviating CO 2 diffusional hindrance in highly loaded amine sorbents. Acting as a mass transport facilitator, water is not the only partner molecule able to enhance bulk CO 2 diffusion. Herein, we show that the enhancing effect of methanol is comparable to that of water in polyethyleniminebased sorbents. Other molecules, such as et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 40 publications
2
38
1
Order By: Relevance
“…10) further confirms the formation of carbamate as a peak at 164.6 ppm appears. The strong electrostatic interactions between R–NH 3 + and –NCOO – , RNH 3 + and surface Si–O – come into play 51 , thus leading to a significantly enhanced rigidity. Interestingly, it was found that a single SLHSP could resist a mechanical compression of 2 N after few minutes exposure to the simulated flue gas.…”
Section: Resultsmentioning
confidence: 99%
“…10) further confirms the formation of carbamate as a peak at 164.6 ppm appears. The strong electrostatic interactions between R–NH 3 + and –NCOO – , RNH 3 + and surface Si–O – come into play 51 , thus leading to a significantly enhanced rigidity. Interestingly, it was found that a single SLHSP could resist a mechanical compression of 2 N after few minutes exposure to the simulated flue gas.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, Andreoli et al formed a solid CO 2 -sorbent by crosslinking PEI (M w 25 000 Da) with fullerene C 60 . [106][107][108] The material's sorption performance has been investigated after conversion to N-doped graphitic carbon via pyrolysis, 109 and improved by spray-drying, 110 and C 60 has also been used to cross-link polypropylenimine (PPI) dendrimers. 111 The reaction of polyamines with aldehyde groups to form imines has been utilised by Hwang et al in cross-linking PEI (M w 25 000 Da) with glutaraldehyde, 112 and by Thompson et al in cross-linking PEI (M w 600 Da), 113 and TEPA, 114 using polyaldehyde phosphorous dendrimers.…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…120 Water has also been shown to have a beneficial effect on CO 2 adsorption capacity and kinetic uptake, to a greater or lesser extent, in many studies in which a polyamine adsorbent is exposed to moisture prior to and/or during adsorption. 27,94,99,108,116 Water may promote adsorption in several ways. Firstly, in the presence of water, the theoretical overall amine efficiency is improved as one mole of CO 2 can react with one mole of amine to form one mole of ammonium bicarbonate, Fig.…”
Section: Materials Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial basis for the use of polyamines with copper was that CO 2 is known to bind to amines to form carbamates. [28][29][30] It was hoped that the amine-CO 2 interaction would lower the activation…”
Section: Introductionmentioning
confidence: 99%